Supporting local adaptive capacity to climate change in the Congo basin forest of Cameroon: a participatory action research approach - Bele, M.Y.; Sonwa, D.J.; Tiani, A.M. (Emerald Publishing Limited, 2013)
This paper aims at assessing the vulnerability of local communities in the Congo basin forests of Cameroon; to help them identify their specific needs for adaptation, and to facilitate knowledge sharing with the aim of enhancing adaptive capacity.Using participatory‐action research approach, research was carried out in two project sites in Nkol‐evodo and in Yokadouma in the Center and South‐East Regions of Cameroon, respectively. The authors shared participatory‐research (PAR) steps and processes to assist other researchers and local stakeholders to jointly assess, monitor and adapt to climatic and other changes.This study shows that the adverse effects of climate conditions to which study communities are exposed are already being felt and exerting considerable stress on most of the important activities to their livelihoods such as agriculture and exploitation of national resources. PAR tools and processes led to participatory diagnosis, conceptualizing of change, participatory identification, prioritization and implementation of specific strategies for climate change adaptation in the study sites. However, further studies are needed to investigate the effectiveness of these strategies.The PAR experiences show that stakeholders' involvement throughout the project needs to be considered by researchers who wish to enhance the adaptive capacity of the communities they work with.This paper contributes to the description of the process for enhancing adaptive capacity of forest living communities. Findings in this research may provide a crucial foundation for community‐based adaptation measures and complement broader‐scale scientific research with local precision.